High-density aluminum-manganese alloy and preparation method thereof
By adding carbon and strontium to the aluminum-manganese alloy and using electromagnetic stirring and refining agent to the aluminum-manganese alloy, the problems of air gap and oxidative slag inclusion in the preparation of aluminum-manganese alloy are solved, and high density and high density aluminum-manganese alloys are achieved, which improves mechanical performance and production efficiency.
Patent Information
- Application Number
- CN202411753706.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
AI Technical Summary
During the preparation process, existing aluminum-manganese alloys are prone to air gaps and oxidative slag inclusions, resulting in poor mechanical and airtight properties, and it is difficult to meet the needs of high density and high density.
By adding carbon and strontium to the aluminum-manganese alloy, combined with electromagnetic stirring and the use of refining agent, the reduction of metal oxides and grain refinement are achieved, and the density and mechanical properties of the alloy are improved.
Aluminum-manganese alloy with high density and high density has high strength and hardness, and is suitable for the preparation of counterweight components, etc., while improving production efficiency and environmental protection performance.
Smart Images

Figure CN119530617A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-density aluminum-manganese alloy and a preparation method thereof, belonging to the technical field of aluminum-manganese alloys. Background Art
[0002] Aluminum alloy is the most widely used nonferrous metal structural material in industry, and has been widely used in aviation, aerospace, automobile, machinery manufacturing, shipbuilding and chemical industries. With the development of the national economy and the advancement of the world economic integration process, its production and consumption have increased significantly.
[0003] As one of the aluminum alloys, aluminum-manganese alloy has excellent corrosion resistance and can be used to manufacture automotive parts, aircraft structures, power equipment, transmission lines, ship parts, building materials, and chemical equipment.
[0004] When aluminum-manganese alloy is used to make counterweight components, etc., a higher density is required.
[0005] Since hydrogen can be dissolved in aluminum or aluminum alloy in large quantities, air gaps, commonly known as pinholes, are generated during the solidification process of aluminum alloy casting due to the precipitation of hydrogen. In addition, oxidized slag is easily generated in the alloy liquid at high temperatures. The generation of pinholes not only reduces the actual cross-sectional area of the casting, but also is a source of cracks, which will seriously affect the mechanical properties of aluminum alloy castings. Therefore, during the preparation process, aluminum-manganese alloy must be refined before pouring to ensure that the alloy liquid is poured into the mold in a very pure state, so as to ensure that the product has good mechanical properties and airtightness. Summary of the invention
[0006] The present invention provides a high-density aluminum-manganese alloy and a preparation method thereof. The high-density aluminum-manganese alloy of the present invention has high density and density, and also has high strength and hardness, and can be used for the preparation of counterweight components and the like.
[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0008] A high-density aluminum-manganese alloy, the chemical composition of which is calculated by weight percentage: Mn: 9-55%, Sr: 0.5-1%, C: 0.2-0.5%, Si≤0.20%, Fe≤0.25%, Cu≤0.10%, B≤0.01%, Pb≤0.02%, Sn≤0.02%, Zn≤0.04%, other single impurities≤0.03%, and Al: balance.
[0009] In the above-mentioned high-density aluminum-manganese alloy, except aluminum, manganese, strontium and carbon, the rest are impurities.
[0010] The high-density aluminum-manganese alloy of the present application has high compactness and density, as well as high strength and hardness, and can be used for the preparation of counterweight components, etc.
[0011] The density of existing aluminum alloys is generally 2.7g / cm 3 The density of the high-density aluminum-manganese alloy in this application can reach 2.87g / cm 3 -7.28g / cm 3 .
[0012] In order to further ensure the quality of the high-density aluminum-manganese alloy, preferably, the mass content of Sr is 0.5-0.8%, and the mass content of C is 0.3%.
[0013] The composition of the alloy has a crucial impact on the performance of the alloy. The preparation method is also very critical. If the conditions are not matched, more oxides and undissolved metals will appear, and the density and internal structure of the alloy will be affected, thereby affecting the degree of alloying. In order to ensure the quality of the high-density aluminum-manganese alloy of this application, this application adopts the following method for preparation:
[0014] The method for preparing the above-mentioned high-density aluminum-manganese alloy comprises the following steps:
[0015] 1) After weighing the molten aluminum, the aluminum molten transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The aluminum molten temperature is 700-780℃;
[0016] 2) After heating the aluminum water to 900-950℃, start the electromagnetic stirring function, the electromagnetic stirring power is: 0.800HZ, add manganese flakes, AlSr10 and graphite powder according to the feeding ratio, the feeding time is ≤80min, and the stirring is continued for 50-80min after the feeding is completed;
[0017] 3) Add 1-3 kg of refining agent per ton of aluminum liquid, start refining, refining time 15-20min, refining temperature: 960-1000℃, argon pressure 0.15-0.20Mpa;
[0018] 4) Remove slag, pour, and perform online degassing before pouring.
[0019] The inventors discovered during the experiment that by adding carbon and strontium to the aluminum-manganese alloy, the metal oxides can be reduced during the preparation process while the grains are refined and integrated with elements such as manganese and aluminum, thereby improving the density and mechanical properties.
[0020] During the preparation of this application, a 25-ton gas-fired tilting furnace was used for production. Electromagnetic stirring was added during the feeding process to shorten the heating process and alloying time, thereby improving efficiency and more than three times the original production capacity.
[0021] This application directly uses molten aluminum to produce aluminum-manganese alloy, eliminating the step of melting aluminum ingots and reducing the burn loss caused by remelting aluminum ingots (generally 2-3% burn loss). Compared with the traditional process of melting 1 ton of aluminum ingots, it saves about 600 degrees of electricity, can reduce 73 kilograms of standard coal, and reduce CO2 emissions by about 130 kg, achieving energy conservation and carbon reduction and reducing costs.
[0022] The molten aluminum used in this application is obtained by electrolyzing molten aluminum oxide. This application has no special improvements on this and will not be described in detail.
[0023] The high-density aluminum-manganese alloy prepared in this application has a denser internal structure, a high degree of cleanliness, and no oxides. The fracture of the obtained high-density aluminum-manganese alloy is enlarged 10 times, and no shrinkage zone, no oxide inclusions, no undissolved metal, fine and uniform crystallization, and good alloying are observed.
[0024] This application does not require the addition of other precious metals such as rare earths.
[0025] In order to further improve the quality of the alloy, in step 2), graphite powder is added first, and then manganese flakes and AlSr10 are added in sequence. The addition time of graphite powder is 5-8 minutes, the addition time of AlSr10 is 10-15 minutes, and the addition time of manganese flakes is 30-40 minutes.
[0026] In order to further improve the refining effect, in step 3), the refining agent is a mixture of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate.
[0027] More preferably, in step 3), the mass ratio of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate is 1:(0.2-0.5):(0.2-0.5):(1-1.3).
[0028] The above refining agent can play an effective refining and purification role through screening and matching promotion according to a specific ratio, without introducing impurity sodium, eliminating the influence of harmful impurities, and effectively reducing smoke and irritating odor, improving the purification effect of the alloy, improving the quality of the alloy, and having a good refining effect. The obtained alloy is dense, delicate and clean, and the dosage is significantly reduced.
[0029] In the above step 3), the mass dosage of the refining agent is 0.5 to 1.5‰ of the mass of the molten aluminum.
[0030] In the above step 4), the slag removal time is ≤25min, and after the slag removal is completed, it is allowed to stand for 10-15min.
[0031] In the above step 4), after the slag is removed, the temperature rises to 950-1000°C, and then casting begins. Before casting, the online degasser is turned on. The power of the degasser is: rotor speed: 90-100rmp, argon flow rate: 40-60L / min.
[0032] After the pouring in step 4) is completed, the ingot stacking robot stacks the ingots.
[0033] The technologies not mentioned in the present invention are all referred to the prior art.
[0034] The high-density aluminum-manganese alloy of the present invention has high density and density, as well as high strength and hardness, and can be used for the preparation of counterweight components, etc.; the preparation process is simple and easy to operate, and easy to industrialize. At the same time, a refining agent suitable for the high-density aluminum-manganese alloy is selected, which improves the quality of the high-density aluminum-manganese alloy and reduces the dosage. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is an end view of the fracture of the high-density aluminum-manganese alloy obtained in Example 1 (magnified 10 times);
[0036] Figure 2 This is an end view of the fracture of the high-density aluminum-manganese alloy obtained in Example 2 (magnified 10 times); DETAILED DESCRIPTION
[0037] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0038] Example 1
[0039] Aluminum Manganese 10 Alloy:
[0040] Raw materials: 99.7% aluminum water, 99.7% manganese flakes, 200 mesh graphite powder and AlSr10.
[0041] Prepare raw materials according to the chemical composition by weight percentage: Mn: 10%, Sr: 0.6%, C: 0.3% and the balance aluminum.
[0042] 1) After weighing the molten aluminum, the molten aluminum transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The molten aluminum temperature is 700-780°C and the weight of the molten aluminum is 20.95 tons.
[0043] 2) After heating the aluminum water to 900°C, start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, add graphite powder according to the chemical composition, the feeding time is 6 minutes, then add manganese flakes, the feeding time is 35 minutes, and finally add AlSr10, the feeding time is 12 minutes, and the stirring is continued for 60 minutes after the addition is completed;
[0044] 3) Add 1 kg of refining agent per ton of aluminum liquid, start refining, refining time 15min, refining temperature: 960℃, start powder spray refining machine, argon pressure 0.15Mpa; the refining agent is a mixture of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate with a mass ratio of 1:0.3:0.3:1;
[0045] 4) Remove the slag for 15 minutes; after removing the slag, let it stand for 10 minutes.
[0046] 5) Start heating up. When the temperature reaches 950°C, start casting. Start the online degasser before casting. The power of the degasser is: rotor speed: 90rmp, argon flow rate: 50L / min. Casting time ≤ 90min.
[0047] 6) Obtain high-density aluminum-manganese alloy, and stack the ingots with an ingot stacking robot.
[0048] This product inspection:
[0049] Product composition detection: Mn: 10.21%, Sr: 0.6%, C: 0.3%, Si: 0.048%, Fe: 0.09%, B: 0.0013%, Pb: 0.0010%, Sn not detected, Zn ≤ 0.0039%, other single impurities ≤ 0.04%, Al: balance.
[0050] The end view of the product fracture is magnified 10 times, see Figure 1 ,Depend on Figure 1 It can be seen from the fracture end face: no shrinkage zone, no oxide inclusions, no undissolved metal, fine and uniform crystallization, and good alloying.
[0051] Product density: 4.87g / cm 3 ; Gas content: 0.028ml / 100gAl; Hardness: 102.74HBw.
[0052] Embodiment 2:
[0053] Aluminum Manganese 20 Alloy:
[0054] Raw materials: 99.7% aluminum water, 99.7% manganese flakes, 200 mesh graphite powder and AlSr10.
[0055] Prepare raw materials according to the chemical composition by weight percentage: Mn: 20%, Sr: 0.6%, C: 0.3% and the balance aluminum.
[0056] 1) After weighing the molten aluminum, the molten aluminum transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The molten aluminum temperature is 700-780°C and the weight of the molten aluminum is 20.85 tons.
[0057] 2) After heating the aluminum water to 900°C, start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, add graphite powder according to the chemical composition, the feeding time is 6 minutes, then add manganese flakes according to the chemical composition, the feeding time is 35 minutes, and finally add AlSr10 according to the chemical composition, the feeding time is 12 minutes, and continue stirring after the addition is completed: 60 minutes;
[0058] 3) Add 1 kg of refining agent per ton of aluminum liquid, start refining, refining time 15min, refining temperature: 960℃, start powder spray refining machine, argon pressure 0.15Mpa; the refining agent is a mixture of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate with a mass ratio of 1:0.3:0.3:1;
[0059] 4) Remove the slag for 15 minutes; after removing the slag, let it stand for 10 minutes.
[0060] 5) Start heating up. When the temperature reaches 950°C, start casting. Start the online degasser before casting. The power of the degasser is: rotor speed: 90rmp, argon flow rate: 50L / min. Casting time ≤ 90min.
[0061] 6) Obtain high-density aluminum-manganese alloy, and stack the ingots with an ingot stacking robot.
[0062] This product inspection:
[0063] Product composition detection: Mn: 20.28%, Sr: 0.6%, C: 0.3%, Si: 0.046%, Fe: 0.05%, Cu: 0.0011%, Pb: 0.0010%, other single impurities ≤ 0.04%, Al: balance.
[0064] The end view of the product fracture is magnified 10 times, see Figure 2 ,Depend on Figure 2 It can be seen from the fracture end face: no shrinkage zone, no oxide inclusions, no undissolved metal, fine and uniform crystallization, and good alloying.
[0065] Product density: 5.28g / cm 3 ; Gas content: 0.026ml / 100gAl; Hardness 219.97HBw.
[0066] Comparative Example 1
[0067] The difference from Example 2 is that Sr is omitted and the omitted Sr amount is supplemented by molten aluminum (0.6%), and the rest is the same as Example 2.
[0068] After the fracture end face of the product is enlarged by 10: compared with Example 2, the grain size is increased by 19.8%.
[0069] Product density: 4.13g / cm 3 ; Gas content: 0.139ml / 100gAl; Hardness: 176.45HBw.
[0070] Comparative Example 2
[0071] The difference from Example 2 is that C is omitted and the omitted C amount is supplemented by molten aluminum (0.3%), and the rest is the same as Example 2.
[0072] After the fracture end of the product was magnified by 10%, there were a few oxide inclusions and undissolved metal (433ppm).
[0073] Product density: 4.01g / cm 3 ; Gas content: 0.107ml / 100gAl; Hardness: 173.28HBw.
[0074] Comparative Example 3
[0075] The difference from Example 2 is that Sr and C are omitted at the same time, and the omitted Sr and C are supplemented with molten aluminum (0.9%), and the rest are the same as Example 2.
[0076] After the fracture end surface of the product was enlarged by 10°, there were a few oxide inclusions and undissolved metal (460 ppm), and the grain size was 23.46% larger than that of Example 2.
[0077] Product density: 3.91g / cm 3 ; Gas content: 0.142ml / 100gAl; Hardness: 156.82HBw.
[0078] Comparative Example 4
[0079] The difference from Example 2 is that the amount of Sr is increased to 1.2% (an increase of 0.6% compared to Example 2), the amount of Al is reduced by 0.6%, and the rest is the same as Example 2. Hardness: 181.23 HBw.
[0080] Comparative Example 5
[0081] The difference from Example 2 is that the amount of Sr is reduced to 0.3% (0.3% less than that of Example 2), the amount of Al is increased by 0.3%, and the rest is referred to Example 2. Hardness 172.36 HBw. The inventor has found in practice that for the aluminum-manganese alloy with a specific composition of this application, too much or too little Sr will affect the hardness of the product. The reason is that the inventor believes that when the amount of Sr is insufficient, the grain fineness is insufficient and the degree of alloying is poor. When Sr is excessive, the alloy will be softened and is not suitable for places with high hardness requirements.
[0082] Comparative Example 6
[0083] The difference from Example 2 is that the C content is increased to 0.7% (an increase of 0.4% compared to Example 2), the Al content is reduced by 0.4%, and the rest is the same as Example 2.
[0084] Product density: 4.98g / cm 3; Gas content: 0.103ml / 100gAl; Hardness: 196.27HBw.
[0085] Comparative Example 7
[0086] The difference from Example 2 is that the refining agent in step 3) is completely replaced by potassium chloride, and the rest is the same as Example 2.
[0087] After the fracture end of the product was magnified by 10%, there were a few oxide inclusions and undissolved metal (212ppm).
[0088] Product density: 3.24g / cm 3 ; Gas content: 0.156ml / 100gAl; Hardness: 119.86HBw.
[0089] Comparative Example 8
[0090] The difference from Example 2 is that the refining agent in step 3) is replaced by a mixture of potassium fluorosilicate and titanium dioxide in a mass ratio of 1:0.3, and the rest is the same as Example 2.
[0091] After the fracture end of the product was magnified by 10%, there were a few oxide inclusions and undissolved metal (221ppm).
[0092] Product density: 3.68g / cm 3 ; Gas content: 0.169ml / 100gAl; Hardness: 132.68HBw.
[0093] Comparative Example 9
[0094] The difference from Example 2 is that the refining agent in step 3) is replaced by a mixture of potassium fluoroborate and potassium sulfate in a mass ratio of 0.3:1, and the rest is the same as Example 2.
[0095] After the fracture end of the product was magnified by 10%, there were a few oxide inclusions and undissolved metal (263ppm).
[0096] Product density: 3.96g / cm 3 ; Gas content: 0.125ml / 100gAl; Hardness: 145.86HBw.
[0097] Comparative Example 10
[0098] The difference from Example 2 is that in step 2), graphite powder is added after adding manganese flakes and AlSr10, and the rest is the same as Example 2.
[0099] After the fracture end of the product was magnified by 10%, there were a few oxide inclusions and undissolved metal (106ppm).
[0100] Example 3
[0101] Aluminum manganese 50 alloy:
[0102] Raw materials: 99.7% aluminum water, 99.7% manganese flakes, 200 mesh graphite powder and AlSr10.
[0103] Prepare raw materials according to the chemical composition in weight percentage: Mn: 50%, Sr: 0.6%, C: 0.3% and the balance aluminum.
[0104] 1) The molten aluminum transfer bag is weighed and directly filled into a 25-ton tilting aluminum melting furnace. The molten aluminum temperature is 700-780°C and the weight of the molten aluminum is 20.15 tons.
[0105] 2) After heating the aluminum water to 900°C, start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, add graphite powder according to the chemical composition, the feeding time is 6 minutes, then add manganese flakes, the feeding time is 35 minutes, and finally add AlSr10, the feeding time is 12 minutes, and the stirring is continued for 60 minutes after the addition is completed;
[0106] 3) Add 1 kg of refining agent per ton of aluminum liquid, start refining, refining time 15min, refining temperature: 960℃, start powder spray refining machine, argon pressure 0.15Mpa; the refining agent is a mixture of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate with a mass ratio of 1:0.3:0.3:1;
[0107] 4) Remove the slag for 15 minutes; after removing the slag, let it stand for 10 minutes.
[0108] 5) Start heating up. When the temperature reaches 950°C, start casting. Start the online degasser before casting. The power of the degasser is: rotor speed: 90rmp, argon flow rate: 50L / min. Casting time ≤ 90min.
[0109] 6) Obtain high-density aluminum-manganese alloy, and stack the ingots with an ingot stacking robot.
[0110] This product inspection:
[0111] Product composition detection: Mn: 50.02%, Sr: 0.6%, C: 0.3%, Si: 0.048%, Fe: 0.09%, B: 0.0013%, Pb: 0.0010%, Sn not detected, Zn ≤ 0.0039%, other single impurities ≤ 0.04%, Al: balance.
[0112] The fracture end face of the product is magnified 10 times, and no shrinkage zone, no oxide inclusions, no undissolved metal are found. The crystals are fine and uniform, and the alloying is good.
[0113] Product density: 7.27g / cm 3; Gas content: 0.022ml / 100gAl; Hardness 576.42HBw.
Claims
1. A high-density aluminum-manganese alloy, characterized in that: The chemical composition includes by weight percentage: Mn: 9-55%, Sr: 0.5-1%, C: 0.2-0.5%, Si≤0.20%, Fe≤0.25%, Cu≤0.10%, B≤0.01%, Pb≤0.02%, Sn≤0.02%, Zn≤0.04%, other single impurities≤0.03%, Al: balance.
2. The high-density aluminum-manganese alloy according to claim 1, characterized in that: The mass content of Sr is 0.5-0.8%, and the mass content of C is 0.3%.
3. The method for preparing a high-density aluminum-manganese alloy according to claim 1 or 2, characterized in that: The steps include: 1) After weighing the molten aluminum, the aluminum molten transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The temperature of the molten aluminum is 700-780℃; 2) After heating the aluminum water to 900-950℃, start the electromagnetic stirring function, the electromagnetic stirring power is: 0.800HZ, add manganese flakes, AlSr10 and graphite powder according to the feeding ratio, the feeding time is ≤80min, and the stirring is continued for 50-80min after the feeding is completed; 3) Add 1-3 kg of refining agent per ton of aluminum liquid, start refining, refining time 15-20min, refining temperature: 960-1000℃, argon pressure 0.15-0.20Mpa; 4) Remove slag, pour, and perform online degassing before pouring.
4. The method for preparing a high-density aluminum-manganese alloy according to claim 3, characterized in that: In step 2), graphite powder is added first, and then manganese flakes and AlSr10 are added in sequence. The addition time of graphite powder is 5-8 minutes, the addition time of AlSr10 is 10-15 minutes, and the addition time of manganese flakes is 30-40 minutes.
5. The method for preparing a high-density aluminum-manganese alloy according to claim 3 or 4, characterized in that: In step 3), the refining agent is a mixture of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate.
6. The method for preparing a high-density aluminum-manganese alloy according to claim 5, characterized in that: In step 3), the mass ratio of potassium fluorosilicate, titanium dioxide, potassium fluoroborate and potassium sulfate is 1:(0.2-0.5):(0.2-0.5):(1-1.3).
7. The method for preparing a high-density aluminum-manganese alloy according to claim 6, characterized in that: In step 3), the mass dosage of the refining agent is 0.5 to 1.5‰ of the mass of the molten aluminum.
8. The method for preparing a high-density aluminum-manganese alloy according to claim 3 or 4, characterized in that: In step 4), the slag removal time is ≤25min. After the slag removal is completed, the mixture is allowed to stand for 10-15min.
9. The method for preparing a high-density aluminum-manganese alloy according to claim 3 or 4, characterized in that: In step 4), after the slag is removed, the temperature rises to 950-1000°C, and then casting begins. Before casting, the online degasser is turned on. The power of the degasser is: rotor speed: 90-100rmp, and argon flow rate: 40-60L / min.